Who bears the cost of NICE public health recommendations?. Issue 1 (19th October 2017) - Hinde, Sebastian; Wiyani, Anggie; Griffin, Susan; Walker, Simon
Abstract: Background: In the UK, NICE issues guidance on public health initiatives. Failure to report which sectors of the economy are affected by their implementation precludes the appropriate accounting for the full opportunity costs, and has the potential to result in erroneous decision making and inefficient budgetary planning. Sources of data: We reviewed all NICE public health guidances available at the time of research, categorizing the sector on which the cost burden of the public health initiatives fall and the extent to which this burden was estimated. Areas of agreement: The majority of guidances were determined to be associated with a cost burden on the NHS ( n = 48) and local authorities' public health spend ( n = 47). Areas of controversy: Explicit identification and quantification of cost burden by sector of the economy was reported for only eight guidances. Growing points: Increasing numbers of research studies are developing methods to robustly consider the implications of cross sector budget impacts. Areas timely for developing research: Future NICE guidance should report disaggregated costs across the sectors where they fall. Further research is needed to conceptualize the opportunity cost of financial burdens falling on non-health budgets before optimal decision making in public health is possible.